Training as a Catalyst for Knowledge Management and Tax Administration Efficiency - Umale Okoh; Muzainah Mansor; Marhaiza Ibrahim (Cita Konsultindo Research Center, 2022)
The quest to improve tax administration efficiency and revenue generation is eminent in all nations. The purpose of this study is to understand the link between training, knowledge management (KM) and tax administration efficiency. Qualitative data were collected from 20 tax officers through face-to-face interview at Federal Inland Revenue Service (FIRS), Nigeria. The qualitative data were supported with documentary study of FIRS annual training schedule. Semi-structured and open-ended interview questions was employed as a guide for the face-to-face interview and recorded with a smart voice recorder. Thematically, the data were analyzed with NVivo 10 qualitative software. Data analysis entails identification and report of themes in line with the research objectives and participants’ responses. Two main themes namely formal and informal training were identified. Furthermore, sub themes identified include induction and inspector of taxes in connection to formal training while technical session and “train the trainer” were linked to informal training. The study found formal and informal training as catalysts that can improve KM and tax administration efficiency. This study recommends training and retraining of tax officers annually in order to improve KM and tax administration efficiency which would increase tax revenue for nation development.